2015
DOI: 10.1111/ajd.12354
|View full text |Cite
|
Sign up to set email alerts
|

Consensus recommendations on the use of daylight photodynamic therapy with methyl aminolevulinate cream for actinic keratoses in Australia

Abstract: Australia has the highest prevalence of actinic keratoses (AK) worldwide. Because of the risk of transformation of AK to invasive squamous cell carcinomas, consensus guidelines recommend that AK are removed using appropriate therapies to prevent progression to invasive disease. Daylight photodynamic therapy (PDT) is emerging as an efficacious treatment for AK, particularly for patients who require treatment of large areas of chronic actinic damage that can be exposed easily to daylight. Daylight PDT with methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 23 publications
5
46
0
2
Order By: Relevance
“…In recent years, multiple clinical studies documented that PDT can be successfully performed with a 2‐hour exposure to natural or simulated daylight, and guidelines on dPDT were established . The introduction of dPDT offered a concept to reduce pain and simplify the procedure while maintaining high efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple clinical studies documented that PDT can be successfully performed with a 2‐hour exposure to natural or simulated daylight, and guidelines on dPDT were established . The introduction of dPDT offered a concept to reduce pain and simplify the procedure while maintaining high efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In European studies daylight PDT can be performed in all weather conditions, but temperatures > 10 °C are advised for patient comfort. Consensus guidelines have also been produced …”
Section: Treatmentmentioning
confidence: 99%
“…It is important to note that these presented times do not serve as a recommendation for treatment times, as there are currently no studies that suggest treatment times as low as these can provide effective dPDT. In fact, it is suggested that treatment times < 1 h may provide insufficient time for photosensitizer production . However, these data can give confidence to practitioners of dPDT that interruptions in the patients’ daylight exposure (e.g.…”
Section: Discussionmentioning
confidence: 99%